THE EFFECT OF PARENTS’ ROLE AND SCHOOL CLIMATE ON ACADEMIC STRESS OF MADRASAH ALIYAH’S STUDENTS IN RURAL AND URBAN AREA - Pramesti, Meta Dwi; Neti Hernawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Adolescence is a period of transition from childhood to adulthood, marked by a “storm-and-stress” phase due to heightened susceptibility to conflicts and mood swings, making adolescents particularly vulnerable to stress. One prevalent form of stress among adolescents is academic stress, influenced by various factors. This study aims to analyze the impact of adolescent characteristics, family dynamics, parental roles, and school climate on the academic stress experienced by Madrasah Aliyah students in both rural and urban areas. The research was conducted across five schools, each representing a different sub-district, namely MA Mathlaul Anwar Barengkok, MA Mathlaul Anwar Cidokom, MA Al-Mukhlisin Ciseeng, MAN 1 Kota Bogor, and MAN 2 Kota Bogor. A purposive sampling approach was used to select 180 students, comprising 86 from rural and 94 from urban settings. Data were analyzed using correlation tests, regression analysis, and independent t-tests. The findings indicated that adolescent girls experience higher levels of academic stress than boys. Additionally, the dimensions of support and pressure showed a significant positive correlation with academic stress, while dimensions related to frequency and school climate did not demonstrate any influence in this study. This research offers important implications for educators and policymakers in developing targeted interventions aimed at alleviating academic stress, particularly through enhancing support systems and managing academic pressures for adolescents in diverse environments.